1993
DOI: 10.1111/j.1559-1816.1993.tb01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Categorization and the Influence of Drug Involvement on Drug Attitude Structures: Implications for Assessing Drug Use and Tolerance in the Workplace1

Abstract: Theories of social categorization were used to generate hypotheses concerning the impact of drug involvement on the attitudes and knowledge structures that people use in making drug‐related judgments. Data indicated that greater drug exposure tended to foster more complex knowledge structures for drugs and drug users as revealed by subjects’ perceptions of drug users, tolerance for drug use, and perceptions of drug seriousness. Basically, high drug involvement in terms of personal alcohol use and associating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…First, why should adolescents differ in their preferred musical style or in their decision to play one instrument rather than another? One answer to this may involve the notion of self-to-prototype matching (see, e.g., Burke & Reitzes, 1981;Cantor, Mischel, & Schwartz, 1982;Chassin, Presson, Sherman, Corty, & Olshavsky, 1981;Cohen, 1981;Holcom, Lehman, & Lord, 1993;Moss & Frieze, 1993;Niedenthal, Cantor, & Kihlstrom, 1985;Niedenthal & Mordkoff, 1991;Price & Bouffard, 1974). This states that a person is more likely to chose one activity or object over another if the prototypical image of the former corresponds more with the person' s own self-image than does the prototypical image of the latter activity/object.…”
Section: Summary and General Discussionmentioning
confidence: 99%
“…First, why should adolescents differ in their preferred musical style or in their decision to play one instrument rather than another? One answer to this may involve the notion of self-to-prototype matching (see, e.g., Burke & Reitzes, 1981;Cantor, Mischel, & Schwartz, 1982;Chassin, Presson, Sherman, Corty, & Olshavsky, 1981;Cohen, 1981;Holcom, Lehman, & Lord, 1993;Moss & Frieze, 1993;Niedenthal, Cantor, & Kihlstrom, 1985;Niedenthal & Mordkoff, 1991;Price & Bouffard, 1974). This states that a person is more likely to chose one activity or object over another if the prototypical image of the former corresponds more with the person' s own self-image than does the prototypical image of the latter activity/object.…”
Section: Summary and General Discussionmentioning
confidence: 99%
“…Unsurprisingly, marijuana users had higher acceptability and lower stigma and legal concerns regarding medical marijuana than nonusers. Past research has found that greater drug exposure is associated with lower perceptions of drug stigma and seriousness (Holcom, Lehman, & Lord, 1993). In addition, whereas nonusers distinguished medical and mixed administration methods with respect to consideration of using medical marijuana, users did not distinguish between the two.…”
Section: Discussionmentioning
confidence: 76%